Nematocidal activity of fungal filtrates on eggs and juveniles of five species of sedentary endoparasitic nematodes - Jumbam B.; Peetz A. B.; Kunwar V. S.; Zhang L.; Zasada I. A.; Aime M. C. (Journal of Nematology)
Research efforts are needed to develop new biocontrol strategies against plant-parasitic nematodes (PPNs) to replace chemicals and maintain sustainable crop production. In this study, filtrates obtained from fungi isolated from cyst nematodes (Heteroderidae) were evaluated for activity against eggs and second-stage juveniles (J2) of five PPNs: Globdera ellingtonae, Heterodera glycines, Meloidogyne incognita, M. hapla, and M. chitwoodi. Initially, filtrates of 42 fungal isolates were evaluated for effects on G. ellingtonae and H. glycines egg viability. After the initial screening, six of the fungal isolates were selected for further evaluation against additional PPN eggs and J2 based upon evidence of usage in other studies, fast growth, and frequency of isolation. Filtrates from Alternaria tenuissima JB217, Fusarium acaciae-mearnsii JB201, Purpureocillium lilacinum JB209, and Trichoderma virens JB98 reduced H. glycines egg viability by >80%. Aureobasium sp. JB70, F. proliferatum JB173, and P. lilacinum JB209 reduced G. ellingtonae egg viability by >50% but had negligible effect on the J2 stage of this nematode. Filtrate from F. acaciae-mearnsii JB201was the most lethal against PPNs, immobilizing ~100% of J2 of all nematode species while filtrate from A. tenuissima JB217 only immobilized J2 of G. ellingtonae, M. chitwoodi, and M. hapla. These fungal filtrates are therefore promising alternative sources of natural bioactive substances for the potential management of PPNs.